Loss prevention : controls and concepts : a creative approach to security applications - Astor, Saul D. (Los Angeles : Security World Pub. Co., 1978)
The book peers skeptically into the practices and concepts of business security and loss prevention. It exposes the wastefulness of many old security practices, and it recommends a new place for loss prevention in the structure of contemporary enterprise.
Includes index.
oif 20/02/2019
Loans
Keywords: Retail trade---Security measures; Inventory shortages---Prevention; Shoplifting; Employee theft